Is the Isodesmic Reaction Approach a Better Model for Accurate Calculation of pKa of Organic Superbases? A Computational Study - Biswas, Abul Kalam; Lo, Rabindranath; Ganguly, Bishwajit (Synlett, 2013)
The acid-base dissociation constant (pKa) can be related to the solubility and binding of drugs. However, measuring accurate pKa values is a challenging task. In this study, we have examined the pKa of various organic superbases: naphthalenes, cyclic guanidines, vinamidines, and acyclic guanidines computationally. We have calculated the pKa of such superbases by employing two methods: a conventional thermodynamic cycle and a second method based on an isodesmic reaction. The thermodynamic cycle involves computation of solvation free energy by using gas-phase free energy and the difference in solvation free energies (∆Gsolv) between products and reactants. Calculations performed with the isodesmic reaction approach do not use the free energy of solvation; hence, the accuracy of the approach is less sensitive to solvent molecules and global charges of the calculated species. The root-mean-square errors (RMSE) predict that the pKa of the studied organic superbases are more accurate when calculated with the isodesmic reaction approach.
Keywords: basicity; dissociation constant; organic superbases; isodesmic reactions